2020
DOI: 10.1371/journal.pone.0230752
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of previously diagnosed diabetes and glycemic control strategies in Mexican adults: ENSANUT-2016

Abstract: Objectives To describe the prevalence of previously diagnosed diabetes among Mexican adults, to characterize the associated risk factors, and to describe which glycemic control strategies are the most used. Methods We analyzed data from 8,631 adults aged �20 years who participated in the ENSANUT-2016 and from whom we gathered data about previously diagnosed diabetes, risk factors, glycemic control strategies, and measures to prevent complications. Results The prevalence of previously diagnosed diabetes in Mexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…10 In China, reports indicate that among people ≥ 60 years, the risk of death was greater among those with two or more NCDs (RR = 2.59) in comparison to those with only one NCDs (RR = 1.79). [11][12][13][14][15][16] This is consistent with our ndings, where risk of death was also greater in adults ≥ 60 years and those with two or more NCDs (RR = 24.1) versus those with one (RR = 14.3).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…10 In China, reports indicate that among people ≥ 60 years, the risk of death was greater among those with two or more NCDs (RR = 2.59) in comparison to those with only one NCDs (RR = 1.79). [11][12][13][14][15][16] This is consistent with our ndings, where risk of death was also greater in adults ≥ 60 years and those with two or more NCDs (RR = 24.1) versus those with one (RR = 14.3).…”
Section: Discussionsupporting
confidence: 91%
“…15 It has been shown that NCDs increase the severity from COVID-19. In a country like Mexico where 49% of adults have hypertension, 16 14% have diabetes, 17 and 24% develop CVD, 18 it is important to quantify the risk of death among the population with NCDs and COVID-19. It is also important to consider the role of the health system providing care to patients with COVID-19 in cases with and without other NCDs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our results suggest that obesity is a COVID- these factors remain to be confirmed by clinical evidence [30]. Given the large proportion of undiagnosed diabetes cases in Mexican and poor glycemic control reported by recent estimates, the burden of COVID-19 might be higher than expected in Mexico and poses a challenge for the Mexican healthcare system to give particular attention to this sector as the epidemic moves forward [31][32][33].…”
Section: Discussionmentioning
confidence: 67%
“…Additional factors which have been proposed to modify COVID-19 mortality risk and worsen glycemic control in diabetes include corticosteroid therapy, inadequate glucose monitoring, the effect of social distancing on diabetes care and the use of antihypertensive medication; however these factors remain to be confirmed by clinical evidence [30]. Given the large proportion of undiagnosed diabetes cases in Mexican and poor glycemic control reported by recent estimates, the burden of COVID-19 might be higher than expected in Mexico and poses a challenge for the Mexican healthcare system to give particular attention to this sector as the epidemic moves forward [31][32][33].…”
Section: Discussionmentioning
confidence: 99%